Potential of second home tourism as a strategy to revive fraser's hill as a tourism destination - Goh, Keng Chai (2008)
Second home tourism has become an emerging sector especially in the western world and it is increasingly importance in certain region due to its positive impacts to the economic sector and tourism industry. Study conducted in Spain revealed that 70% of the second home ownerships are locals. Second home tourism will be having great potential growth especially in the global level due to the increasing aged population by 2050. In Malaysia, second home tourism is still young and mainly targeting the foreigners through the MM2H programme. Fraser's Hill, it is truly an idyllic place for anyone to rest and to escape from not only the heat and humidity but also the hustle and bustle of city life. It is one of the prettiest Malaysian Hill resorts with cool climate and proximity to the Klang Valley, which is an ideal retreat for city dwellers. However, it seems not been well perceived either by the locals and foreign visitors in recent years. Seasonality and lack of activities as well as amenities/facilities in Fraser’s Hill had makes it less attractive to visitors during the low season periods due to the shortcoming of its attractions. Tourist arrivals and average occupancy rates of hotels/resorts have declined and tourism industry players have lamented this problem to the federal government. The problems faced by Fraser’s Hill has then tested through the study to implement second home tourism as a potential strategy to enhance the occupancy rate and length of stay by the long-stay guests or second homers especially during the low season periods which will not only stimulate the accommodation sector to operate at economical and sustainable level but also creates another opportunity on the demand growth on local services and facilities which would bring to the better improved facilities and infrastructure and development. This study also investigated the concept/variant of second home and reviewed the success/failure of second home tourism practices in Malaysia.